The Impact of the Doha Trade Proposals on Farmers' Incomes in China - Yang, Jun (2012)
This paper analyzes the potential impacts of the Doha trade proposals (those of the USA, EU and G20) on agricultural production and incomes of China's farmers by region and income group. By linking a global trade model to a national policy model which itself is connected to a set of disaggregated household data, we are able to assess the effects of the proposed Doha trade liberalizations on households both at the national and regional levels. According to the results of the model, the impacts of a Doha Round agreement on households differ significantly from those of China's WTO accession. China's economy would benefit from the trade liberalization associated with the Doha Round. The overall impacts, however, are relatively minor. Although farmers will benefit at the national level, the gains among farmers vary largely by income group and province. Also, the impacts on households that produce different types of crops differ.